AN ANALYSIS ON GRAMMATICAL ERRORS OF STUDENTS’ WRITING ASSIGNMENT USING SIMPLE PRESENT TENSE MADE BY EIGHT GRADE STUDENTS OF SMPN 5 PAMEKASAN - Evha Nazalatus Sa'adiyah Sy; Chairunnisa Chairunnisa (The Ellite of Unira, 2018)
This study aim to find what kinds of grammatical errors made by eight grade students in writing assignment of SMPN 5 Pamekasan? This study is qualitative research by using descriptive approach. The data of this study were taken by using a test. The test was in the form of written test by asking students to make paragraphs. And the test itself is in the written form, and it was used as the research instrument. It was taken in the eight grade SMPN 5 Pamekasan through 2017-2018 academic year. And the test was held for about 60 minutes that consists of 21 students. Based data analysis it is found the greatest errors categories are errors in omission which dedicated 28 times or 44,4 %. For the second error domination, on the other hand, there is the errors of addition and misformation which appeared 15 times by 23,8 %. And the lowest frequency occurrences is the errors of misordering which only has 5 times with the percentage 7,9 %.